Diabetic foot resulting in amputation: our experience - Patel, K. G.; Thekdi, Pukur I.; Patel, Naman K.; Patel, Nita K.; Thekdi, Komal P. (International Journal of Research in Medical Sciences, 2017)
Background: The aim of our study was to early diagnosis of diabetic foot so that the complications can be prevented, to control the systemic infection and prevent the complications, to study the effectiveness of regular dressing in diabetic foot so as to prevent the local spread of infection and the ulcer and to conclude that early diagnosis, care and proper meticulous treatment of diabetic foot can prevent amputation. Methods: The present study was prospective, observational and longitudinal. Protocol of the procedure was formed along with Performa, Patient Information Sheet, Informed Consent Form and approval from Ethical Committee. The present study was carried out in surgery department of C.U Shah medical college, Surendranagar; Gujarat state. The study was carried out from 1st August 2011 to 30th September 2013. A total of one hundred patients admitted in surgery ward with diabetes type 1 or 2 with ulcer on foot having grade 1 or 2 of Wagner’s classification without any other co morbid condition. These patients undergo daily dressing with various dressing solutions according to their ulcer characteristics. All the patients given diet/oral hypoglycaemic drug/insulin for control of diabetes. Antibiotics given according to the infective status of the patients. Patients were either completely treated, went under skin grafting or ended up with amputation were recorded. Results: Of 100 cases studied, youngest patient was 32 years and oldest was 80 years of age. Highest number of cases was found in the age group 61-70 years (30%). Of the 100 cases studied in this series 36 (36%) patient were having Wagner’s class 1 ulcer and 64 (64%) patient having class 2 ulcers. Of 100 cases, various surgical treatment given to the patients according to the ulcer. In that 65(65%) debridement, 20 (20%) Incision & drainage, 10 (10%) STG, 5 (5%) fasciotomy. Most of the patients were undergone basic surgical procedure which is debridement on the 7th day follow up, out of 100 cases 70 patients came for follow up. Out of 70, all patients having healing ulcer. Out of 70 patients, 15(21.43%) patients were underwent STG on 15th day and other 55 (71.57%) patients having healing ulcer advised daily dressing with follow up after 1 week. Out of 30 patients, 3 (10%) patients underwent amputation on 7th day of follow up. On the 15th day new 5 (16.67%) patients underwent amputations, so total number of amputation done till date was 8 (26.67%). On 21st day, new 7 (23.34%) patients were underwent amputations and total number of amputations till date were 15 (50%). On 30th day, new 15 (50%) patients underwent amputations. Conclusions: Foot ulceration in diabetic patients is a resource consuming, disabling morbidity that often is the first step towards lower extremity amputation. Prevention is the best treatment.